A Pembangunan Aspek Estetika Game Edukasi Berbasis Massively Multiplayer Online - Fajar Darmawan; Abdi Lazuardi Pratama; Handoko Supeno (Universitas Widyatama, 2022)
Campus online MMO RPG is a game that can be used as a simulation for new students who are unable to come to campus for orientation due to a contagious epidemic. Therefore, the Campus Online MMORPG game also requires visuals that can make new students as players feel what the visuals on campus are like, making players feel comfortable when studying and how the culture on campus can be imagined by new students. Due to the need for visualization in games so that new students can imagine the environment on campus as in the real world, it is necessary to create an aesthetic that can represent the shape on campus so that students themselves can experience being on campus like the real world and feel comfortable when playing and learning through games. This research was conducted to produce an aesthetic that can describe life on campus. The research was conducted by conducting a literature study through existing research. By doing a combination between FBE and DGBL. As well as conducting testing using the Likert scale success measurement from the questionnaire. The result of this research is an aesthetic that can describe life on campus virtually through video game media, and increase the convenience of learning for players.